Cancer Stem Cells in Human Prostate Cancer. Role in Drug Resistance and Metastasis (International Journal of Medical and Surgical Sciences, 2015)
Prostate cancer is one of the most important causes of oncologic death in men, and Chile has also reached that level. Prostate cancer mortality is mostly associated with metastatic disease where the cancer is usually resistant to available treatments, particularly hormone- therapy and chemotherapy. It has been suggested that the existence of cancer stem cells could account for the metastatic capacity and treatment resistance in most cancers. Recently, cells with stem characteristics have been identified in established cell lines and animal models of prostate cancer. We have isolated and characterized this kind of cells from patient tumors. This finding opens the possibility to manipulate them as potential therapeutic targets.
Keywords: Prostate cancer; Cancer stem cells; Drug resistance; Metastasis